How talking cures : revealing Freud's contributions to all psychotherapies - Jaffe, Lee (Dialog-on-Freud series., 2014)
In this book, Lee Jaffe argues that comparisons of all approaches to talking cures, and decisions about the choice of treatment for a given patient can be grounded in an understanding of the essential ways that each therapeutic procedure works.